Análisis del principio de buena fe y lealtad procesal en el procedimiento ejecutivo, Unidad Judicial Civil del cantón Guaranda, año 2021. - Mazón Silva, Luis Fernando (2023)
The present investigation addresses the problem of procedural abuse and the transgression of the principle of good faith and procedural loyalty in the processing of the executive procedure, despite the fact that the law establishes that the procedural parties must act within the framework of legality and avoid actions fraudulent and fraudulent actions to hinder the progress of the procedure, this is not fulfilled within the Justice Administration, although the executive procedure contemplates clear rules with regard to prior exceptions and establishes that these must be raised only when the respective support is available. Evidentiary and they should not be interposed in order to delay compliance with the obligation contained in any executive title, what is sought with the investigation carried out is to raise awareness among legal professionals so that there is no abuse of the right and respect each of the rules, rights and principles of the Ecuadorian legal system. The research is carried out under a mixed approach in which the qualitative and quantitative method was applied, thus allowing the collection of information that was duly analyzed, the survey and interview technique of these methods was applied in order to collect reliable data regarding the problem analyzed, as a relevant result of the investigation, it is established that in the Civil Judicial Unit of the Guaranda canton there is a lack of application of the principle of good faith and procedural loyalty with regard to the processing of the executive procedure. Keywords: Procedural abuse, Good faith, Procedural loyalty, Executive procedure, Principle.